An Analysis on Turkish Market Entry Opportunities: the Case of Lithuanian Dairy Companies - Jamontaite, Kamile; Ahmedova, Saida; Okumus, Abdullah; Ozturk, Selen (Ekonomika, 2017)
In the present research, authors examine Turkish market entry opportunities for three leading dairy companies in Lithuania. This study focuses on evaluating firms’ export performance opportunities and combining them with selected export market potential factors. For this purpose, the case-study method was used through personal interviews with export managers of three leading Lithuanian dairy companies in 2016, conducted in order to determine the factors affecting their Turkish market entry. Using a cross-case analysis, comparisons were made between different companies’ entry opportunities. According to the results, Lithuanian dairy companies can be described as being passive about the Turkish market. Its market protection politics, implemented by the Turkish government, could be named among the main reasons. From the first sight, this fact makes the Turkish market unattractive for European dairy producers. However, the study shows that, after doing some more detailed market research, new potential opportunities can appear.
Keywords: Lithuanian dairy sector; Turkish market entry; export barriers; export performance; marketing strategy